2016
DOI: 10.1002/jeab.221
|View full text |Cite
|
Sign up to set email alerts
|

Syntax for calculation of discounting indices from the monetary choice questionnaire and probability discounting questionnaire

Abstract: The 27-item Monetary Choice Questionnaire (MCQ; Kirby, Petry, & Bickel, 1999) and 30-item Probability Discounting Questionnaire (PDQ; Madden, Petry, & Johnson, 2009) are widely used, validated measures of preferences for immediate versus delayed rewards and guaranteed versus risky rewards, respectively. The MCQ measures delayed discounting by asking individuals to choose between rewards available immediately and larger rewards available after a delay. The PDQ measures probability discounting by asking individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(61 citation statements)
references
References 32 publications
(53 reference statements)
1
54
0
Order By: Relevance
“…Indeed, GDPs obtained higher scores than controls on the "non-planning" and "lack of premeditation" subscales of the BIS-11 questionnaire and the UPPS Impulsive Behavior Scale, respectively, implying that those individuals are more oriented to the present rather than the future and tend to act without consideration of the consequences. In this line, an association between scores on both subscales and discounting rates has been previously reported (61,76,77). Altogether, this pattern of results is likely to contribute to the tendency of GDPs to favor immediate bets, despite the negative consequences of their gambling behavior.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Indeed, GDPs obtained higher scores than controls on the "non-planning" and "lack of premeditation" subscales of the BIS-11 questionnaire and the UPPS Impulsive Behavior Scale, respectively, implying that those individuals are more oriented to the present rather than the future and tend to act without consideration of the consequences. In this line, an association between scores on both subscales and discounting rates has been previously reported (61,76,77). Altogether, this pattern of results is likely to contribute to the tendency of GDPs to favor immediate bets, despite the negative consequences of their gambling behavior.…”
Section: Discussionsupporting
confidence: 62%
“…To analyze choice impulsivity, a two-way ANOVA was computed on k-values obtained at the MCQ, with MAGNITUDE (small, medium, large) as the within-subject factor and GROUP (HCs, GDPs) as the between-subject factor. Importantly, as several works reported that using the natural log (nlog) transformation allows to approximately normalize the distribution of k-values (61,62), analyses were performed on nlog k-values.…”
Section: Self-reported Measuresmentioning
confidence: 99%
“…For each item, individuals were presented with a choice between a smaller immediate reward and larger delayed reward at one of three magnitudes (small, $25-35; intermediate, $50-60; large, $75-85; see Supplementary Table 3). The overall response pattern was used to infer temporal discounting functions (k) ranging from .00016-.25 29 , with larger values reflecting greater devaluation of delayed rewards (higher bias for immediate gratification). Values of k were obtained for the three reward magnitudes and were averaged to obtain the final dependent measure.…”
Section: Delay Discountingmentioning
confidence: 99%
“…To assess impulsivity, participants performed a 27-item Monetary Choice Questionnaire (MCQ) at the end of each session (1215h), which measures delayed discounting by asking individuals to choose between smaller rewards available immediately and larger rewards available after a delay (Gray, Amlung, Palmer, & MacKillop, 2016;Kirby, Petry, & Bickel, 1999). Individual indifference points were determined and discounting rates (overall k-values) calculated.…”
Section: Methodsmentioning
confidence: 99%